"This has more to do with who I am than with my skills" – Student teacher subjectification in Finnish teacher education. (April 2015) - Lanas, Maija; Kelchtermans, Geert
Abstract: This article addresses the argument that in order to offer responsive teacher education which acknowledges student teachers as active members in their education process, teacher educators need to know more about who student teachers are. The context of the research is Finland, in which teacher education is highly selective. The interest in this article is on the process of shaping and re-shaping of student teacher-selves in response to the surrounding implicit norms – a process of student teacher subjectification. Using purposefully constructed narrative data and thematic analysis we identified how students negotiate the implicit social and cultural expectations towards teachers. Highlights: We provide new knowledge of student teacher subjectification in highly selective teacher education (Finland). We identify the social and cultural expectations towards potential teachers as students have come to understand them. We show the process of shaping and re-shaping of student teacher-selves in response to the surrounding implicit norms. We identify different margins of freedom students have when negotiating different elements of normative teacher images.